The Crisis of Polytheism in Late Bronze Ugarit: Crises and Perspectives - de Moor, Johannes С. (1986)
Papers Read at the Joint British-Dutch Old Testament Conference Held at Cambridge, UK, 1985 = Oudtestamentische Studien, Deel 24